Perbedaan Status Karies Pada Anak Sekolah Dasar Yang Mengkonsumsi Air Minum dari Air Pah dan Air PDAM di Kecamatan Musuk Kabupaten Boyolali - Utami, Tri, Dwi Kurniawati, S.KG, MPH, drg. Suyadi (2015)
People who lived in Musuk, Boyolali were consuming drink water from different water resources, PDAM and PAH. Drink water sourced from PAH didn't contain fluoride and its pH was lower than PDAM has, thus people who drank PAH water were at dental caries risk. Dental caries was an infection disease that could damage teeth structure. DMF-T index was commonly used to indicate dental caries issue. The purpose of this study was to find out caries status differences between student who drink water sourced from PAH and the one sourced from PDAM at Musuk, Boyolali. This was analytical cross sectional observational study. The research was located at Musuk, Boyolali on November 16th, 2014. Ninety seven students of 6th grade elementary treated as sample, chosen by proportional random sampling method. DMF-T index and questionnaire filling were utilized to obtain dental caries data from each sample. Sample of PDAM and PAH water were registered on fluoride level and pH balance measurement. Mann-Whitney test was used for data analysis. The study output showed average 0,316 ppm fluoride level of PDAM water with 7,5 pH balance, while PAH water at 0 fluoride level with 6 pH balance. Dental caries issue of people consuming PDAM water were at 2,4 DMF-T index (low category) while people consuming PAH water has 3,7 DMF-T index (moderate category). Statistic test delivered 0,002 significance value or p<0,05 which showed significant differences of caries status between PDAM water and PAH water.